2009
DOI: 10.3892/or_00000346
|View full text |Cite
|
Sign up to set email alerts
|

Significant overexpression of Hsp110 gene during colorectal cancer progression

Abstract: Abstract. Colorectal cancer (CRC) is one of the most frequent malignant diseases in the world. Metastatic spread of the cancer to the lymph nodes is a crucial factor for progression and therapeutic management of the disease. We analysed gene expression profiles of CRC patiens by lowdensity cancer-focused oligonucleotide microarrays to identify new predictive markers of the extent of the disease and for better understanding of CRC progression. Relative expression levels of 440 genes known to be involved in canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 22 publications
1
36
0
Order By: Relevance
“…TCTP was overexpressed in many human cancer tissues including liver (42), colorectal (43), prostate (44), breast (45), and lung cancer (46). Similarly, TCTP was detected in pancreatic cancer cell lines, and malignant duct epithelial cells and some normal acinar cells but not normal pancreatic duct epithelial cells adjacent to tumor foci.…”
Section: Discussionmentioning
confidence: 97%
“…TCTP was overexpressed in many human cancer tissues including liver (42), colorectal (43), prostate (44), breast (45), and lung cancer (46). Similarly, TCTP was detected in pancreatic cancer cell lines, and malignant duct epithelial cells and some normal acinar cells but not normal pancreatic duct epithelial cells adjacent to tumor foci.…”
Section: Discussionmentioning
confidence: 97%
“…Only a few previous studies, which were conducted with small colorectal cancer sample sizes, reported that HSP110 overexpression was associated with worse overall survival, advanced stage and nodal metastasis in colorectal cancer. 36,37 In these circumstances, the study by Dorard et al 25 provided important clues about the effect of HSP110 mutations on colorectal cancer. It is reasonable that the increased expression of mutant HSP110 inhibits the normal functions of HSP, which are beneficial to cancer cell survival; therefore, this molecular alteration can result in positive effects on survival in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…TCTP protein levels are upregulated in cancer cells and in human tumours (Tuynder et al, 2004;Kim et al, 2008a;Ma et al, 2009;Slaby et al, 2009). Downregulation of TCTP has been implicated in biological models of tumour reversion (Tuynder et al, 2002(Tuynder et al, , 2004, and the protein is the target of various anticancer drugs (Tuynder et al, 2004;Efferth, 2005), of which one has entered a phase-I/II clinical trial (Telerman and Amson, 2009).…”
Section: Introductionmentioning
confidence: 99%